Diversity of soil organic carbon and water characteristics under different vegetation types in northern Bengkulu, Indonesia - Bandi Hermawan; HERY SUHARTOYO; BAMBANG SULISTYO; BAMBANG GONGGO MURCITRO; WELLY HERMAN (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Hermawan B, Suhartoyo H, Sulistyo B, Murcitro BG, Herman W. 2020. Diversity of soil organic carbon and water characteristics under different vegetation types in northern Bengkulu, Indonesia. Biodiversitas 21: 1793-1799. Organic carbon and water characteristics are important soil properties that can easily degrade following the conversion of forest to cultivation land, but their levels of degradation depend on successive vegetation types after deforestation. The research aimed to evaluate the spatial diversity of soil organic carbon (SOC) and water characteristics on sites with annual and cash crops, as well as natural vegetation types. Forty-two undisturbed and disturbed soil samples were collected at 0-10 and 10-20 cm depths from plantation areas (rubber and oil palm), rice fields, shrub land, and grassland in Mukomuko, North Bengkulu, and Central Bengkulu Regencies of Bengkulu Province, Indonesia. Vegetation types were observed, and soil water characteristics were determined using a pressure plate apparatus unit from undisturbed soil samples, while SOC and particle-size distribution were analyzed from disturbed soil samples. The uppermost 10 cm soil layers were dominated by organic-C intervals of more than 3.0% while the 10-20 cm depths had intervals of less than 3.0%. Soils under oil palm and rice production had higher SOC of above 6.0% and water availability at the field capacity of 0.4-0.6 g g-1, particularly at 0-10 cm depths, while those under rubber and grass had a lower status of measured variables, particularly at 10-20 cm depth. There was a strong relationship (R2 = 0.63) between the soil organic carbon and water availability among study soils, suggesting the possibility to predict potential soil water deficits from organic matter status.